Combined effect of both surface finish and sub‐surface porosity on component strength under repeated load conditions - Alison J. McMillan; Rhys Jones (Engineering Reports, 2020)
Abstract High duty engineering component life is usually demonstrated through extensive testing and statistical analysis applied to empirical curve‐fit equations. Because of this, the extent of the testing required is huge and costly: it must consider the load cycle range and test to high numbers of cycles. Additive Manufacturing (AM) for high duty components has brought to the fore the question of the effect of porosity and surface roughness on fatigue life, and how the true life of a critical component can be assessed conservatively. The authors propose the first step toward the development of a fatigue model based on well‐established engineering physics principles, by creating computational specimens with modeled surface roughness and porosity, and subjected to cyclic loading using Finite Element Analysis. They show that the combination of roughness features and sub‐surface pores leads to an equivalent plastic strain distribution pattern that suggests an emergent physical process that has not been reported before, and which indicates that the component strength and life reduction arising from surface roughness can be made significantly worse by the presence of porosity. The development of such phenomenological understanding should lead to improved life prediction techniques, more cost effective test procedures, and the development of better AM methods.